Different Patellar Indices and Their Role in Decision-Making: An MRI-Based Study - Raju, Sivashanmugam; Chinnakkannu, Karthikeyan; Balakumar, Balasubramanian; Sundareyan, Ramanivas; Kaliappan, Saravanakumar P.; Puttaswamy, Mohan K. (The Journal of Knee Surgery, 2020)
Magnetic resonance imaging (MRI) of knee has become the integral part of knee evaluation, hence any MRI based study adds more value if it helps in the decision-making process, especially for surgery in treating patellofemoral pain. We tried to determine normal patellar indices using knee MR images and the correlation between them and also compared the results with different ethnic population. We analyzed the prospectively collected MR images of 117 knees/patients, and Insall–Salvati (IS) index, modified IS index, patellotrochlear (PT) index, and patellophyseal (PP) index were calculated. Two standard deviations from the mean were used to define the normal and abnormal patellar position. Cohen's kappa values were used to assess the agreement between the indices and the correlation between them was analyzed using Pearson's correlation. The mean values for IS index, modified IS index, PT index, and PP index were 1.00, 1.53, 0.40, and 0.58, respectively. There was very good agreement between PT index and PP index. There was weak correlation between all the indices except the one between PT and PP indices which had a strong negative correlation. Based on commonly used methodology, there were 4% of asymptomatic patients who were outside the standardized cut-off values and different indices classified different knees as abnormal. This indicates patellar position should be one among the many other factors, not as a sole factor when making a surgical decision in patellofemoral pain. We also noted that the indices compared fairly with other populations. Further research is needed to determine the clinical applicability of these indices.
Keywords: patella; knee; patellofemoral pain; patellotrochlear index; patellophyseal index; MRI knee